Cooperative pathogenicity in cystic fibrosis: Stenotrophomonas maltophilia modulates Pseudomonas aeruginosa virulence in mixed biofilm - Pompilio, Arianna; Crocetta, Valentina; De Nicola, Serena; Verginelli, Fabio; Fiscarelli, Ersilia; Di Bonaventura, Giovanni (Frontiers in Microbiology, 2015)
The present study was undertaken in order to understand more about the interaction occurring between S. maltophilia and P. aeruginosa, which are frequently co-isolated from CF airways. For this purpose, S. maltophilia RR7 and P. aeruginosa RR8 strains, co-isolated from the lung of a chronically infected CF patient during a pulmonary exacerbation episode, were evaluated for reciprocal effect during planktonic growth, adhesion and biofilm formation onto both polystyrene and CF bronchial cell monolayer, motility, as well as for gene expression in mixed biofilms. P. aeruginosa significantly affected S. maltophilia growth in both planktonic and biofilm cultures, due to an inhibitory activity probably requiring direct contact. Conversely, no effect was observed on P. aeruginosa by S. maltophilia. Compared with monocultures, the adhesiveness of P. aeruginosa on CFBE41o- cells was significantly reduced by S. maltophilia, which probably acts by reducing P. aeruginosa's swimming motility. An opposite trend was observed for biofilm formation, confirming the findings obtained using polystyrene. When grown in mixed biofilm with S. maltophilia, P. aeruginosa significantly over-expressed aprA, and algD - codifying for protease and alginate, respectively - while the quorum sensing related rhlR and lasI genes were down-regulated. The induced alginate expression by P. aeruginosa might be responsible for the protection of S. maltophilia against tobramycin activity we observed in mixed biofilms. Taken together, our results suggest that the existence of reciprocal interference of S. maltophilia and P. aeruginosa in CF lung is plausible. In particular, S. maltophilia might confer some selective “fitness advantage” to P. aeruginosa under the specific conditions of chronic infection or, alternatively, increase the virulence of P. aeruginosa thus leading to pulmonary exacerbation.